Pendidikan Karakter Jujur Melalui Kantin Kejujuran - Asnila Delpi; Rengga Satria (Prodi Pendidikan Keagamaan Islam, 2023)
This study examines the problems of Islamic Religious Education teachers in fostering the morals of class XI students at SMK Negeri 7 Padang. The purpose of this study is to find out how and what the problems of Islamic Religious Education teachers are in fostering morals. Then how the solutions to problems of Islamic Religious Education teachers in fostering morals in class XI SMK Negeri 7 Padang. The method used in this research is the qualitative method. The population of this study was teachers of Islamic Religious Education, class XI students of SMK Negeri 7 Padang with a sample of 6 respondents. Data collection techniques in this study used observation, interviews, and documentation. The results of this study indicate that (1) the problems of Islamic Religious Education teachers in fostering morals are the lack of morals towards Allah SWT, oneself, teachers, friends, and society, (2) the problems of Islamic Religious Education teachers in fostering morals towards the environment are students who lack obedience to school regulations, poor manners, lack of self-awareness of students, and lack of sensitivity to the environment, (3) The solution to the problems of Islamic Religious Education teachers in fostering student morals is to give directions to students, approach students, teach them students, make habituation to students, create a good environment, and establish communication with various parties.